The Role of the Indonesian Police in Mitigating the Impact of Man-Made Disasters in Indonesia - Wita Agustina; Widana, IDK Kerta; Christine Sri Marnani; Pujo Widodo; Kusuma (Formosa Journal of Science and Technology, 2024)
Indonesia is a country that is vulnerable to various disasters, both natural and man-made. Man-made disasters, which are often caused by negligence or criminal acts such as fires, riots, and terrorism, have a serious impact on the security and welfare of society. This research aims to explore the role of the Indonesian National Police (Polri) in the prevention, mitigation and recovery after man-made disasters in Indonesia. Using national security theory and man-made disaster theory as a frame of reference, this research identifies the steps taken by the National Police to maintain national stability and security in the face of man-made disasters. Polri is involved in intelligence, patrol, counseling, evacuation, law enforcement, and post-disaster community recovery. Through the utilization of advanced technology, specialized training, and collaboration with related agencies, Polri seeks to prevent and mitigate the impact of man-made disasters. The results of this study provide an in-depth insight into the effectiveness of Polri's strategies and actions in dealing with man-made disasters, as well as its contribution to public security and order. The research concludes that Polri has a crucial role to play in protecting the safety and well-being of the community amidst the threat of man-made disasters.